Sharea Issues in the Application of Takaful: Review on Islamic Law Perspective - Suharto, Suharto; Fasa, Muhammad Iqbal (Hunafa: Jurnal Studia Islamika, 2017)
Insurance is still debated between scholars when viewed in the light of Islamic law. Contemporary Muslim jurists are fully aware that the legal status of Insurance not been determined by Islamic law thinkers in advance (jurists). The application of TakÄful today is the result of a struggle between the understanding of Islami law with the reality of what happened. Thus, the problem needs to be reviewed in the light of Islamic law in depth. This paper attempts to offer Shariah Issues in the Application of TakÄful From Islamic Law Perspective, including The Concepts of TakÄful (Sharia Insurance), Legal Basis of TakÄful (Sharia Insurance), History of TakÄful (Shariah Insurance) Development, Scholars' Views on TakÄful (Sharia Insurance), The Principles of TakÄful (Sharia Insurance), Establishment of Contract in TakÄful (Sharia Insurance), and To Compare The Characteristics Between TakÄful (Shariah Insurance) and Commercial Insurance.